A Latent Implementation Error Detection Method for Software Validation - Jiantao Zhou; Jing Liu; Jinzhao Wu; Guodong Zhong (Journal of Applied Mathematics)
Model checking and conformance testing play an important role in software system design and implementation. From the view of integrating model checking and conformance testing into a tightly coupled validation approach, this paper presents a novel approach to detect latent errors in software implementation. The latent errors can be classified into two kinds, one is called as Unnecessary Implementation Trace, and the other is called as Neglected Implementation Trace. The method complements the incompleteness of security properties for software model checking. More accurate models are characterized to leverage the effectiveness of the model-based software verification and testing combined method.